Globalization of Financial Markets and Implications for Pacific Basin Developing Countries - Goldsbrough, David (IMF Working Papers; Working Paper ;, 1991)
This paper analyzes the consequences of the growing interdependence of world financial markets for Pacific developing countries. Section I discusses trends in financial integration in the Pacific and the underlying movements in saving and investment. Section II seeks to quantify the increased capital mobility, in terms of rate of return differentials and the degree of correlation between savings and investment rates across countries. Section III focuses on policy implications of increasing integration, including the effectiveness of macroeconomic policy instruments, the usefulness of the current account as a target of policy, and the dangers of excessive taxation of financial intermediation.